Qualitative Study Of Elderly Independence In Fulfilling Daily Living Activities In Sindang RW 03 Margasari Village Tasikmalaya District - Pratama, Oktarian; Putri Puspitasari (Sean Institute, 2023)
The aging process occurs naturally. This can lead to physical, mental, social, economic and psychological problems. Physical changes in the elderly will affect, especially in fulfilling the activities of daily life of the elderly themselves. Objective: This study aims to determine the level of independence of the elderly in fulfilling daily living activities in Kp. Sindang RW 03 Margasari Village. Method: the method used in this research is analytical descriptive research with a qualitative approach, using source triangulation techniques, where the instruments were interview form and observation form. Results: Key respondents need the help of others or loved ones to carry out their daily activities. Conclusion: The capacity of key respondents in fulfilling the needs of daily living activities requires several other people, because it is influenced by the physical condition of the elderly themselves due to falls. Suggestion: It is recommended for families to provide support to the elderly in order to increase the independence of the elderly in activities, especially in the elderly with dependence so that the quality of life of the elderly is getting better